2017
DOI: 10.1007/s10763-017-9807-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Competency Demands in Mathematical Tasks: Recognising What Matters

Abstract: In more and more countries, the goal of mathematics education is to develop students' mathematical competence beyond procedural and conceptual knowledge. Thus, students need to engage in a rich variety of tasks comprising competencies such as communication, reasoning and problem solving. In addition, assessment tasks should be constructed to measure the particular aspects of mathematical competence to align assessment with curriculum. Teachers need to be able to recognise competency demand in the mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
(65 reference statements)
0
14
0
1
Order By: Relevance
“…Students need to engage in a wide variety of activities, such as reasoning, communicating, connecting, modelling and problem-solving. Teachers should be able to identify their competence needs in activities they want to use in teaching or measuring in mathematical activities (Pettersen & Nortvedt, 2018). In this context, the targeted process skills must be reflected in an effective approach to the problem activities used for the development or measurement of ML.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students need to engage in a wide variety of activities, such as reasoning, communicating, connecting, modelling and problem-solving. Teachers should be able to identify their competence needs in activities they want to use in teaching or measuring in mathematical activities (Pettersen & Nortvedt, 2018). In this context, the targeted process skills must be reflected in an effective approach to the problem activities used for the development or measurement of ML.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…In a study by Lestari, Juniati and Suwarsono (2017), the views of high school teachers towards ML, their habits in mathematics teaching, and their beliefs in integrating ML's mathematics into learning-teaching were examined. In the study conducted by Pettersen and Nortvedt (2018), teachers' and preservice teachers' competence needs in the activities were determined using an item analysis tool. Concerning competencies (communication, devising strategies, mathematization, representation, symbols and formalism, reasoning and argumentation), each of the teachers and pre-service teachers used a tool about mathematical efficiency and efficiency requirements of activities.…”
Section: Relationship Between ML and Problem Posingmentioning
confidence: 99%
“…Teachers should be able to determine competency requirements in mathematical activities, which they want to use for teaching or measurement purposes (Pettersen & Nortvedt, 2018). In this context, targeted process skills should be reflected in an effective approach to the problem activities used for the development or measurement of ML.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Öğretmenler matematiksel etkinliklerde öğretim ya da ölçme amaçlı kullanmak istedikleri yeterlik ihtiyaçlarını belirleyebilmelidirler (Pettersen & Nortvedt, 2018). Bu bağlamda hedeflenen süreç becerileri MOY'nin gelişimi ya da ölçülmesi için kullanılan problem etkinliklerine etkili bir yaklaşım ile yansıtılmalıdır.…”
Section: Tartışma Ve Sonuçlarunclassified
“…Besides that, it was shown that with PAs, students developed their confidence to tackle complex mathematical problems (Novita et al, 2012). Other scholars (e.g., Pettersen, 2017) have also stressed a need for students to showcase their competencies like communicating mathematically, mathematical reasoning, and problem-solving. It has been stressed that mathematical problem-solving tasks should trigger higher-order thinking and reasoning among learners.…”
Section: Discussion and Implications Of The Research Findingsmentioning
confidence: 99%